2012
DOI: 10.1007/s00244-011-9735-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bioaccumulation and Biomarker Responses in Dreissena polymorpha and D. bugensis After Exposure to Resuspended Sediments

Abstract: The zebra mussel Dreissena polymorpha is widely used as sentinel organism for the assessment of environmental contamination in freshwater environments. However, in the River Rhine (Germany), the D. polymorpha population is declining, whereas the closely related quagga mussel D. bugensis is found in high numbers at some sites. In the present laboratory study, D. polymorpha and D. bugensis were exposed to resuspended native sediments for ≤2 weeks. Wet sediments (<63 μm, 100 mg l(-1) dry weight) were used as surr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 45 publications
4
15
0
Order By: Relevance
“…The statistical evaluation of data outlined insignificant interspecies differences for the studied biomarkers, although in general consistently higher expression of all endpoints considered was observed for D. polymorpha. Inconsistent interspecies differences in susceptibility to contaminants for the two dreissenids have been previously reported by Schäfer et al, (2012) who have recorded in a laboratory study significantly higher DNA damage in the gills of D. bugensis, and conversely significantly higher heat-shock protein content (hsp70) in D.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The statistical evaluation of data outlined insignificant interspecies differences for the studied biomarkers, although in general consistently higher expression of all endpoints considered was observed for D. polymorpha. Inconsistent interspecies differences in susceptibility to contaminants for the two dreissenids have been previously reported by Schäfer et al, (2012) who have recorded in a laboratory study significantly higher DNA damage in the gills of D. bugensis, and conversely significantly higher heat-shock protein content (hsp70) in D.…”
Section: Discussionsupporting
confidence: 55%
“…D. bugensis was proven to allocate more energy to soft tissue relative to shell length (Roe and MacIsaac, 1997), has higher assimilation efficiency (Baldwin et al, 2002), grows faster (Baldwin et al, 2002;Karatayev et al, 2011;Le et al, 2011), filters at a higher rate (Diggins, 2001;Veltman et al, 2008) and was reported to have a lower respiration rate (Stoeckmann, 2003). Interspecies differences were also found for the accumulation of metals and organic contaminants, in general with higher contaminant burdens in D. polymorpha (Rutzke et al, 2000;Richman and Somers, 2005;Schäfer et al, 2012;Matthews et al, 2015). In the meantime, while several studies have addressed the interspecies variability in biomarker responses to chemical stress in different aquatic invertebrates, in the case of dreissenids these issues have seldom been addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its high invasive potential, zebra mussel populations have been recently reported to decline such as in the Rhine River [80] or in the Seine River where some populations seem to have disappeared since a dozen years (personal observations). In the meantime, the closely related quagga mussel D. rostriformis bugensis [81] became in turn invasive in Europe and North America.…”
Section: The Usefulness Of Another Dreissenid Species D Rostriformimentioning
confidence: 99%
“…Some studies focused on differential xenobiotics accumulation between the two species, mostly on metals and given scarce or inconclusive information [92][93][94][95]. Schäfer et al [80] also showed differences between D. polymorpha and D. rostriformis in the bioaccumulation potential of pesticides from resuspended sediments. They showed that quagga mussel accumulates more organochlorine pesticides, with greater DNA damage and lower stress protein hsp70 content.…”
Section: The Usefulness Of Another Dreissenid Species D Rostriformimentioning
confidence: 99%
“…In aquatic systems, bivalves are recognized as important biomonitors because of their ubiquity, abundance, easy sampling, and filter‐feeding lifestyle. Dreissenid mussels are useful monitoring organisms because they usually dwell in large numbers and are well adapted to naturally stressful environments . Dreissenid mussels in the Great Lakes have been used to monitor chemical contaminant levels for over two decades by the NOAA MWP and in recent years for mussel health assessment .…”
Section: Introductionmentioning
confidence: 99%